2016
DOI: 10.5812/traumamon.28590
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Non-Structural Vulnerabilities of Hospitals Involved in the 2012 East Azerbaijan Earthquake

Abstract: Background: When disasters strike, hospitals are among the first units whose efficient and timely services can be crucial and decisive in reducing mortality and rescuing the injured. Non-structural components are among domains that need to be considered in any assessment of hospitals' readiness tools. Objectives: Given that Azerbaijan, and especially the metropolis of Tabriz, is located in the world's earthquake belt, this study aimed to evaluate the non-structural vulnerability of hospitals involved in the 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…From these scores, the authors defined thousands of hospitals reflecting their likelihood to retain functionality during disasters. The WHO Hospital Safety Index has been used extensively across several continents (Heidaranlu et al 2017;Rockenschaub and Harbou 2013;Norman et al 2012;Djalali et al 2014). However, it is limited in that it is not focused on evaluating hospital surge preparedness and it contains items that are not applicable to every hospital.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From these scores, the authors defined thousands of hospitals reflecting their likelihood to retain functionality during disasters. The WHO Hospital Safety Index has been used extensively across several continents (Heidaranlu et al 2017;Rockenschaub and Harbou 2013;Norman et al 2012;Djalali et al 2014). However, it is limited in that it is not focused on evaluating hospital surge preparedness and it contains items that are not applicable to every hospital.…”
Section: Discussionmentioning
confidence: 99%
“…This concept is well described in the Institute of Medicine work titled Crisis Standards of Care: A Systems Framework for Catastrophic Disaster Response (2012). As noted by Heidaranlu et al (2017), achievement of optimal hospital disaster response depends on effective management of these events. The challenge to hospitals can be daunting.…”
Section: Introductionmentioning
confidence: 99%
“…The study has obtained data by utilizing a cross-sectional self-administered questionnaire that was constructed based on the literature review and pilot study. Moreover, the assessment tool has been structured based on literature review, which has revealed that there are many HDP tools and checklists with different scopes and magnitudes, but all of these studies have agreed on the fact that there is no consensus exists on standardized, comprehensive, and validated instrument to assess HDP for all hazards (Heidaranlu, Ebadi, et al, 2017;Heidaranlu et al, 2015;Jenkins et al, 2009;Kaji et al, 2008;Nekoie-Moghadam et al, 2016). Therefore, this study has utilized Hospital Safety Index (HIS) assessment criteria, which was develop by World Health Organization (WHO) in order to define the level of preparedness for each indicator.…”
Section: Methodsmentioning
confidence: 99%
“…When natural disasters, such as flood, earthquake or man-made disasters (terrorist and war attack) occur, the importance of medical facilities is the most considerable (1). As data from the emergency events database (EM-DAT) of the centre for research on the epidemiology of disasters show, the global disaster rate is increasing (2).…”
Section: Introductionmentioning
confidence: 99%
“…If a disaster strikes a country, all political, economic and cultural infrastructures are threatened. However, all equipment and facilities must be mobilized to respond to the crisis (1). Furthermore, FHs are health care units with mobile or fix structures.…”
Section: Introductionmentioning
confidence: 99%